2019
DOI: 10.1002/ca.23345
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the fusion of the ischiopubic synchondrosis using predictive modeling

Abstract: Flaring of the ischiopubic synchondrosis at the time of fusion is a common clinical observation in pediatrics and represents a normal physiological process in skeletal maturation. When presenting unilaterally, this flaring can mimic a range of serious pathological conditions such as osteomyelitis, osteal tumors, and traumatic injury. An improved understanding of ischiopubic synchondrosis fusion is therefore critical to avoid potential misdiagnosis. Retrospective multi-slice computed tomography pelvic scans of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…In a recent study by Gregory et al on CT images, ischiopubic ramus synchondrosis closure was very important in age determination. It has been shown that ischiopubic ramus synchondrosis begins and continues at age 7–13 in boys and 4–9 years in girls [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Gregory et al on CT images, ischiopubic ramus synchondrosis closure was very important in age determination. It has been shown that ischiopubic ramus synchondrosis begins and continues at age 7–13 in boys and 4–9 years in girls [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fusion of the IPS has been shown to be strongly age-related and usually occurs in girls between the age of 4 and 9 years and in boys between the age of 7 and 13 years (Gregory et al 2019 ). Although our findings are in general similar, we found a VND in a 22-year-old female patient with a 5-month history of left-sided groin pain and the referral diagnosis of a primary bone tumor ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the ischium and pubic bone fuse without any clinical symptoms. Fusion is typically observed between the ages of 4 and 9 years in females and 7 and thirteen in males [ 3 ]. However, some children may experience pain and limitation of movement associated with enlargement of the IPS and delayed fusion of the ischium and pubis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%